2013
DOI: 10.1371/journal.ppat.1003487
|View full text |Cite
|
Sign up to set email alerts
|

Tetherin/BST-2 Antagonism by Nef Depends on a Direct Physical Interaction between Nef and Tetherin, and on Clathrin-mediated Endocytosis

Abstract: Nef is the viral gene product employed by the majority of primate lentiviruses to overcome restriction by tetherin (BST-2 or CD317), an interferon-inducible transmembrane protein that inhibits the detachment of enveloped viruses from infected cells. Although the mechanisms of tetherin antagonism by HIV-1 Vpu and HIV-2 Env have been investigated in detail, comparatively little is known about tetherin antagonism by SIV Nef. Here we demonstrate a direct physical interaction between SIV Nef and rhesus macaque teth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(93 citation statements)
references
References 63 publications
4
89
0
Order By: Relevance
“…In contrast, SIV Nef and HIV-2 Env do not mediate tetherin degradation but rather lead to tetherin's intracellular sequestration following enhanced internalization from the surface. This is dependent on AP2 binding sites in both viral proteins (18,(36)(37)(38)49). For Nef (36) and also for Env, as shown here, this does not require the presence of the endocytic signal in tetherin itself.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In contrast, SIV Nef and HIV-2 Env do not mediate tetherin degradation but rather lead to tetherin's intracellular sequestration following enhanced internalization from the surface. This is dependent on AP2 binding sites in both viral proteins (18,(36)(37)(38)49). For Nef (36) and also for Env, as shown here, this does not require the presence of the endocytic signal in tetherin itself.…”
Section: Discussionsupporting
confidence: 50%
“…Most SIVs that lack a vpu gene antagonize their species' tetherins with Nef (15,16). SIVmac Nef binds to the cytoplasmic tail of macaque tetherin and likely forms a ternary complex with clathrin adaptor protein complex 2 (AP2) (36,37) to stimulate tetherin endocytosis and intracellular sequestration. Nef's specificity for primate tetherins depends on a (G/D)DIWK motif that is absent from human tetherin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bst2 has also been shown to activate the NF-B pathway, presumably further amplifying cellular stress signals (17). While the functional roles of Bst2 in uninfected cells are just emerging, it is clear that many viruses encode proteins that subvert Bst2's antiviral activities, often by altering clathrin-mediated endocytic pathways (18)(19)(20). To date, studies aimed at understanding Bst2's role in preventing viral infection have been limited to immune cells and rapidly dividing cell types such as fibroblasts (21).…”
mentioning
confidence: 99%
“…It has been shown that human tetherin (also termed BST2) interacts with Vpu (456)(457)(458)(459)(460)(461)(462)(463) and Nef (464). Meanwhile, CD4 physically binds to Vpu (14,19,433) and Nef (465).…”
Section: Vpu-tetherin/cd4-nef Associationmentioning
confidence: 99%